Parents’, Students’ and Teachers’ Understanding of Sexuality Education - Pokharel, Sharmila (Education and Development, 2020)
School-based sexuality education is regarded as an effective way to increase young people’s understanding of sexually transmitted infections including human immunodeficiency virus infection, unintended pregnancies, abortion, violence, infertility, gender, sexual orientation, etc. This article identifies different perspectives of comprehensive sexuality education in our school’s strategy of teaching sexuality education especially from parents, students and teachers, and to identify the need for CSE in the Nepalese context. This paper has used primary data of qualitative nature. The data were collected from a school’s students where twenty students from grade nine, ten mothers of the students, and three HPE teachers from different schools were selected for study purpose. The collected data were analyzed following thematic approach. Based on the study, the curriculum was not found sufficient for providing sexuality education. Topics related to human rights, gender equality, and sexual and gender diversity were not addressed sufficiently. The teaching method was found to be heavily lecture-based, while the class environment was not comfortable for many students. Data show that providing school-based comprehensive sexuality education can be challenging. Teachers need adequate training to revise their sexual attitude and biases, highlight gender and sexual rights, and promote instruction that makes use of students’ critical thinking skills.